Relationship between methylation status of vitamin D-related genes, vitamin D levels, and methyl-donor biochemistry - Emma Louise Beckett; Konsta Duesing; Charlotte Martin; Patrice Jones; John Furst; Katrina King; Suzanne Niblett; Zoe Yates; Martin Veysey; Mark Lucock (Journal of Nutrition & Intermediary Metabolism, 2016)
Vitamin D is known for its role in the regulation of gene expression via the vitamin D receptor, a nuclear transcription factor. More recently, a role for vitamin D in regulating DNA methylation has been identified as an additional mechanism of modulation of gene expression. How methylation status influences vitamin D metabolism and response pathways is not yet clear. Therefore, we aimed to assess the relationship between plasma 25-hydroxycholecalciferol (25(OH)D) and the methylation status of vitamin D metabolism enzyme genes (CYP2R1, CYP27B1 and CYP24A1) and the vitamin D receptor gene (VDR). This analysis was conducted in the context of dietary vitamin D, and background methyl donor related biochemistry, with adjustment for several dietary and lifestyle variables. Percentage methylation at CpG sites was assessed in peripheral blood cells using methylation sensitive and dependent enzymes and qPCR. Standard analytical techniques were used to determine plasma 25(OH)D and homocysteine, and serum folate and B12, with the relationship to methylation status assessed using multi-variable regression analysis. CYP2R1 and VDR methylation were found to be independent predictors of plasma 25(OH)D, when adjusted for vitamin D intake and other lifestyle variables. CYP24A1 was related to plasma 25(OH)D directly, but not in the context of vitamin D intake. Methyl-group donor biochemistry was associated with the methylation status of some genes, but did not alter the relationship between methylation and plasma 25(OH)D. Modulation of methylation status of CYP2R1, CYP24A1 and VDR in response to plasma 25(OH)D may be part of feedback loops involved in maintaining vitamin D homeostasis, and may explain a portion of the variance in plasma 25(OH)D levels in response to intake and sun exposure. Methyl-group donor biochemistry, while a potential independent modulator, did not alter this effect.